A2B adenosine receptor antagonists rescue lymphocyte activity in adenosine-producing patient-derived cancer models. Issue 5 (17th May 2022) - Tay, Apple Hui Min; Prieto-Díaz, Rubén; Neo, Shiyong; Tong, Le; Chen, Xinsong; Carannante, Valentina; Önfelt, Björn; Hartman, Johan; Haglund, Felix; Majellaro, Maria; Azuaje, Jhonny; Garcia-Mera, Xerardo; et al.
Abstract : Background: Adenosine is a metabolite that suppresses antitumor immune response of T and NK cells via extracellular binding to the two subtypes of adenosine-2 receptors, A2 ARs. While blockade of the A2A ARs subtype effectively rescues lymphocyte activity, with four A2A AR antagonists currently in anticancer clinical trials, less is known for the therapeutic potential of the other A2B AR blockade within cancer immunotherapy. Recent studies suggest the formation of A2A AR/A2B AR dimers in tissues that coexpress the two receptor subtypes, where the A2B AR plays a dominant role, suggesting it as a promising target for cancer immunotherapy. Methods: We report the synthesis and functional evaluation of five potent A2B AR antagonists and a dual A2A AR/A2B AR antagonist. The compounds were designed using previous pharmacological data assisted by modeling studies. Synthesis was developed using multicomponent approaches. Flow cytometry was used to evaluate the phenotype of T and NK cells on A2B AR antagonist treatment. Functional activity of T and NK cells was tested in patient-derived tumor spheroid models. Results: We provide data for six novel small molecules: five A2B AR selective antagonists and a dual A2A AR/A2B AR antagonist. The growth of patient-derived breast cancer spheroids is prevented when treated with A2B AR antagonists. To elucidate if this depends on increased lymphocyte activity, immune cells proliferation, and cytokine production, lymphocyte infiltration was evaluated and compared with the potent A2A AR antagonist AZD-4635. We find that A2B AR antagonists rescue T and NK cell proliferation, IFNγ and perforin production, and increase tumor infiltrating lymphocytes infiltration into tumor spheroids without altering the expression of adhesion molecules. Conclusions: Our results demonstrate that A2B AR is a promising target in immunotherapy, identifying ISAM-R56A as the most potent candidate for A2B AR blockade. Inhibition of A2B AR signaling restores T cell function and proliferation. Furthermore, A2B AR and dual A2A AR/A2B AR antagonists showed similar or better results than A2A AR antagonist AZD-4635 reinforcing the idea of dominant role of the A2B AR in the regulation of the immune system.